Artificial intelligence (New Jersey : Everest Production, 2008)
When does a mere machine become a morally responsible entity? What are the problems that could arise from intelligent machines with super human capabilities? For decades science fiction writers have been intrigued with the idea of creating intelligent machines with physical and mental capabilities far superior to those of human beings. Some leading thinkers predict that human-like robots with intelligence that will be indistinguishable from human beings will be a reality by 2030 to 2040. But how will this impact opportunities and the quality of life for human beings? How will it impact our culture?
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format
Keywords: Artificial intelligence